Green Financing for Sustainable Development in Saudi Arabia - AL-HARBI, Ahmad (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025, 2025)
In my paper, I explore the critical role of green financing in promoting sustainable development within Saudi Arabia. I begin by defining green financing and its significance in facilitating investments in projects that yield environmental benefits while driving economic growth. The paper highlights how green financing aligns with Saudi Arabia's Vision 2030 agenda, essential for the nation’s economic diversification and ecological sustainability. I present a comprehensive analysis of the historical context and evolution of green financing, followed by an examination of its economic and environmental implications, including its capacity to create jobs and reduce carbon emissions. Case studies of successful initiatives, such as the Sakaka Solar Power Project and the Red Sea Project, illustrate the practical benefits of green financing in achieving sustainable development goals. Ultimately, I conclude that green financing is indispensable for Saudi Arabia’s future, advocating for enhanced collaboration between the public and private sectors to foster a sustainable and economically viable future.